Advantages of dynamic bi-directional applanation tonometry in primary open-angle glaucoma diagnostics - A. Sh. Zagidullina; B. M. Aznabaev; I. A. Lakman; R. R. Islamova; R. R. Sattarova (Российский офтальмологический журнал, 2019)
Purpose. To study tonometry parameters features, measured by different methods, taking into account individual morphometric eye parameters and biomechanical properties of the corneoscleral shell in patients with the initial and the advanced stages of primary open angle glaucoma (POAG).Material and methods. 51 patients (99 eyes) aged 48–82, with the initial (45 eyes) and advanced stages (54 eyes) of POAG were examined. The control group consisted of 31 patients (62 eyes) aged 47–83 without ophthalmic pathology. In addition to standard ophthalmologic examination, tonometry was performed using the Ocular Response Analyzer (ORA, Reichert Inc., the USA).Results. The main tonometry parameters of ORA revealed significant differences between POAG patients and the control group. No significant difference in the central corneal thickness (CCT) was found between the POAG and the control group. Patients with I and II stages of glaucoma taken separately showed differences in CCT and tonometry parameters.Conclusion. Dynamic bi-directional applanation tonometry enables to take into account the changes in viscoelastic properties of the corneoscleral eye shell, and definitely has diagnostic advantages in examining patients with various stages of POAG.